Scientific Opinion on the substantiation of a health claim related to Bifidobacterium animalis subsp. lactis LMG P-21384 and changes in bowel function (ID 2940, further assessment) pursuant to Article 13(1) of Regulation (EC) No 1924/2006 - EFSA Panel on Dietetic Products, Nutrition and Allergies (EFSA Journal, 2012)
Following a request from the European Commission, the Panel on Dietetic Products, Nutrition and Allergies (NDA) was asked to provide a scientific opinion on a health claim pursuant to Article 13 of Regulation (EC) No 1924/2006 in the framework of further assessment in relation to Bifidobacterium animalis subsp. lactis LMG P-21384 and changes in bowel function. The food constituent that is the subject of the health claim, B. animalis subsp. lactis LMG P-21384, is sufficiently characterised. The claimed effect, changes in bowel function such as reduced transit time, more frequent bowel movements, increased faecal bulk, or softer stools may be a beneficial physiological effect, provided that it does not result in diarrhoea. No human intervention studies were provided from which conclusions could be drawn for the scientific substantiation of the claim. On the basis of the data presented, the Panel concludes that a cause and effect relationship has not been established between the consumption of B. animalis subsp. lactis LMG P-21384 and changes in bowel function.